RISK AND SAFETY ANALYSIS MODEL FOR PETROL FILLING STATIONS - AHMED, MIRZA MUNIR (2012)
A petrol filling station (PFS) is a common facility that is available in urban and rural areas. It is the only source to supply fuel for automobiles. They store and sell a highly flammable liquid. A PFS has potential hazards to the people, asset, and environment. Variety of hazards such as fire hazards, static electricity, fuel tank explosions, transportation hazards, air pollution evoked by aromatic organic compounds are found to be the major causes of accident/incident occurrences at PFS. The risk posed by these hazards varies from one PFS to another. Many companies are using different risk assessment methods to priorities hazards related to their work activities. Studies related to address importance of safety measures at PFS was not sufficient, noticeably in developing countries. In this study, a new risk and safety analysis model for PFS is to be developed. In this study, 3.5 years data of non-compliances was collected from 2500 PFS located in various cities in Pakistan. The significant numbers of health safety and environment (HSE) non-compliances recorded were due to various factors during operation and maintenance of PFS. The HSE non-compliances were classified into two categories i.e. hazards contributing factors and incident occurrences [fatality (F), accident (A), incident (I) and near miss (NM) cases]. The hazards contributing factors were then further classified into 8 categories. These were Housekeeping (HK), Transportation Hazard (TH), Slips, Trips and Falls (STF), Carelessness (C), Fire Risk (FR), Electrical Faults (EF), Miscellaneous Cases (MC) and Medical Treatment Cases (MTC). A monthly, quarterly and seasonal categorization of HSE non-compliances was carried out to evaluate the hazard occurrences flow pattern for the two categories. The risk assessment of the hazards was carried out and prioritized by using three ditTerent widely used risk assessment methods. These were, risk ranking criterion, risk matrix criterion and as low as reasonably practicable (ALARP).